Trophic structure of fish fauna along the longitudinal gradient of a first-order rural stream - Nimet,Jardel (2015)
Abstract Aim: This study evaluated the trophic structure of the fish assemblage along the longitudinal gradient of a first-order rural stream. Methods Fish were sampled by electrofishing technique in December 2007, September 2008 and March 2009, at three stretch of the Itiz stream (headwater, middle and mouth). We sampled 1,255 individuals relating to 18 species. The categorization of trophic guilds was based on stomach content data of 1,096 individuals, analyzed according to the volumetric method, except for four species, which were classified according to the literature. To test the hypothesis of differences in the richness, abundance and biomass of trophic guilds along the headwater-mouth gradient, it was performed non-parametric statistical analysis of the dietary data. Was also calculated, the amplitude of trophic niche (Levins's index) for each guild. To summarize the composition and abundance of the trophic guilds along the longitudinal gradient, we applied a non-metric multidimensional scaling (NMDS). Results We registered seven guilds: herbivorous, detritivorous, aquatic insectivorous, terrestrial insectivorous, invertivorous, omnivorous and piscivorous, the latter was exclusive to headwater and middle stretches. The omnivorous guild was not recorded in the headwater. Through PERMANOVA analysis it was found that the species richness of more specialized guilds (detritivorous and insectivorous terrestrial) and of generalist invertivorous increased, while less specialized guilds like aquatic insectivorous and herbivorous, decrease significantly in headwater-mouth direction. Except by the non-expected increase of insectivorous terrestrial and decrease of herbivorous downstream, the non-metric multidimensional scaling (NMDS) identified longitudinal variations in abundance and biomass of the guilds that agree with general patterns of fish guilds distribution along environmental gradients. Conclusion These results suggest that the influence of environmental conditions around the stream (local particularities) also contributed to the formation of the observed patterns of trophic guilds along its longitudinal gradient.